Incorporating subjectively-derived behavioral responses into traditional tests of criminal decision-making: a research note - Bouffard, Jeffrey A. (Criminal justice studies, 2025)
In the study of criminal decision-making, researchers commonly present participants with a hypothetical offending scenario and ask how likely participants would be to engage in a list of behavioral responses predetermined by the researchers. Recently, scholars have questioned the use of predetermined response sets and argued instead that participants should be allowed to self-report their own behavioral responses. Using a hypothetical assault scenario presented to separate samples of incarcerated persons and university students, the current study invited participants to evaluate a traditional, predetermined (PD) list of behavioral response options and also to report any additional subjectively-derived (SD) behaviors in which they might engage. The study then explored the added value of including the SD responses. Results indicate that in a few cases, the use of the additional SD response revealed novel behaviors not captured in the list of PD behaviors (mostly alternative forms of prosocial behaviors). Furthermore, when novel SD behaviors were reported, they generally were not the behaviors that participants indicated they would be most likely to actually engage in. Mindful of these findings, the value of SD responses in the study of criminal decision-making is discussed.